SIPEBI: A Model of Cultural Edutainment Web Portal as a Medium for Students’ Self-Directed-Learning and Alternative Assessment - Dony Saputra; Santo Tjhin; Tubagus Zufri (Bandar Lampung University (UBL), 2014)
As the growth of e-learning, students centric learning were adopt to explore more on student directed learning especially in early years learner. On subject such as Science, Math and English have a various website or portal which can accommodate the learner desired to learn more with the subject he or she choose in an interactive and fun way in gaining learning experience. The website and portal also give the teachers an alternative way to teach and assess the students regarding that subject in an interactive and fun way. But there were no web portal that designated for social and cultural study, especially for local content. So the students have no alternative way to learn our culture and the teacher also doesn’t have any alternative way to teach and asses the students for this subject. To solve this problem, this research is experimenting in creating an interactive cultural edutainment web portal called Surya Iconic PusatEdukasiBudaya Indonesia (SIPEBI) that can be used by the student or teacher as a pre-elementary study. The method that we use is an explanatory with an experimental approach by designing and creating a web portal. Result of this research is the creation of cultural edutainment web portal that can accommodate students’ self-directed learning and teachers’ alternative way to teach and assess students’ knowledge on cultural study by exploring the website